Specific Clinical and Biological Features Characterize Inflammatory Bowel Disease–Associated Colorectal Cancers Showing Microsatellite Instability - Svrcek, Magali; El-Bchiri, Jamila; Chalastanis, Alexandra; Capel, Emilie; Dumont, Sylvie; Buhard, Olivier; Oliveira, Carla; Seruca, Raquel; Bossard, Céline; Mosnier, Jean-François; Berger, Françoise; Leteurtre, Emmanuelle; et al. (Journal of clinical oncology, 2007)
Microsatellite instability (MSI) due to mismatch repair (MMR) deficiency has been reported to occur at variable frequencies in inflammatory bowel disease-associated intestinal neoplasias (IBD-Ns). We investigated a large series of IBD-N for associations between MSI and several biologic and clinical parameters related to tumors, patients, and their treatment. A total of 277 IBD-Ns in 205 patients were screened for MSI. Biologic and clinical variables of patients with high levels of DNA microsatellite instability high (MSI-H) were collected and compared with those associated with 33 MSI-H non-IBD colorectal cancers (CRCs). A total of 27 IBD-Ns from 17 patients were found to be MSI-H. Compared with sporadic MSI-H CRCs, patients presented with a younger age at diagnosis, and there was no female predominance and no right-sided predominance. Unlike sporadic MSI-H CRCs, MSI-H IBD-Ns presented with heterogeneous mismatch repair defects involving MLH1, MSH2, MSH6, or PMS2, and a low frequency of MLH1 promoter methylation. They exhibited frequent BRAF mutations and frameshift mutations in genes containing coding repeat sequences. The mechanisms underlying MMR deficiency in MSI-H IBD-Ns are different from those in sporadic MSI-H tumors and seem to be more related to those observed in hereditary MSI-H tumors. However, BRAF mutations were observed in MSI-H IBD-Ns, similar to sporadic MSI-H tumors, but unlike hereditary MSI-H tumors. Finally, the mutational events in target genes for instability are the same in MSI-H IBD-N tumors as in non-IBD sporadic and hereditary colorectal MSI-H cancers, indicating a colon-related repertoire of target gene alterations.